Development and validation of a novel scoring system to predict severe intraventricular hemorrhage in very low birth weight infants - He, Longkai; Zhou, Wei; Zhao, Xiaopeng; Liu, Xiaoping; Rong, Xiao; Song, Yanyan (Brain & development (Tokyo. 1979), 2019)
We sought to develop and validate a novel scoring system for the prediction of severe intraventricular hemorrhage (SIVH) in very low birth weight infants (VLBWI). This retrospective cohort multicenter study included 615 VLBWI born between 24 and 32 weeks gestational age (GA). Multivariable logistic regression analyses were used to determine which factors evaluated within the first 5 days of life were associated with SIVH and the weights of these variables. The accuracy of the predictive scoring system was prospectively tested in the same units. The final SIVH scoring system included the following variables: antenatal steroid therapy, GA, birth weight (BW), 1-min Apgar score, mechanical ventilation and hypotension. The SIVH scores used to divide the subjects into three tiers (low-risk (<5), moderate-risk (5–8) and high-risk (>8)) were developed based on these variables. Of infants with a score below 5, 1.2% (4/339) developed SIVH. Of those with a score above 8, 42.5% (17/40) developed SIVH. The scores were successfully verified in 99 VLBWI. These findings suggest that among infants with a score >8, the incidence of SIVH is significantly higher. This scoring system can be used to predict the incidence of SIVH during the first 5 days after birth and may contribute to the early intervention in and prevention of SIVH.